Gregory of Nyssa, Contra Eunomium II : an English version with supporting studies : proceedings of the 10th International Colloquium on Gregory of Nyssa (Olomouc, September 15-18, 2004) - Karfíková, Lenka.; Douglass, Scot, 1961-; Zachhuber, Johannes.; Hall, Stuart George.; Gregory, of Nyssa, Saint, approximately 335-approximately 394. (Vigiliae Christianae, Supplements, 2007)
The volume contains the contributions presented during the 10th International Colloquium on Gregory of Nyssa, Contra Eunomium II , held in Olomouc, the Czech Republic, on September 15-18, 2004. It is organized into four major sections: (I) Two papers (Th. Kobusch, B. Studer) that contextualize the main problematic of the Second Book Against Eunomius - the theory of language and the problem of naming God - from a broader philosophical and theological perspective; (II) a new English translation of the text (S. G. Hall); (III) a series of main papers providing commentary on its passages (Th. Böhm, M. Ludlow, Ch. Apostolopoulos, A. Meredith, J. Zachhuber, L. Karfíková, J. S. O'Leary, V. H. Drecoll); and (IV) numerous short essays discussing related philosophical (E. Moutsopoulos, G. Arabatzis, J. Demetracopoulos, L. Chvátal, Th. Alexopoulos, G. Lekkas, T. Tollefsen), as well as theological (T. Dolidze, S. Douglass, A. Ojell, A.-G. Keidel, T. Aptsiauri, J. Rexer) issues.